Complementarity Between Foreign Aid and Financial Development as a Driver of Economic Growth in Selected Emerging Markets - Kunofiwa Tsaurai (Comparative Economic Research. Central and Eastern Europe, 2018)
This paper studied whether the complementarity between financial development and foreign aid promotes economic growth in selected emerging markets using the panel Fully Modified Ordinary Least Squares (FMOLS) approach, with data ranging from 1994 to 2014. Although (1) aid-growth and (2) finance-growth studies have been conclusively dealt with, the role of financial development in the aid-growth nexus has been hardly researched. Is financial development a channel through which foreign aid positively influences economic growth? The current study seeks to address these issues using selected emerging markets as a case study. The complementarity between foreign aid and financial development (domestic credit provided by the financial sector, domestic private credit provided by banks, outstanding domestic private debt securities and stock market turnover) resulted in a significant positive impact on economic growth. The study, therefore, urges selected emerging markets to implement policies which deepen the financial sector in order to allow foreign aid to positively contribute towards economic growth.
Keywords: F35; F43; G15; 330; foreign aid; financial development; economic growth; emerging markets